1993
DOI: 10.1111/j.1365-2427.1993.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and turnover ofHyalella aztecain central Ontario, Canada compared with other regions

Abstract: 1. Hyalella azteca (Amphipoda) inhabiting macrophyte beds in eight Canadian Shield lakes were sampled during the ice-free seasons of 1984 and 1985. These amphipods were found to be predominantly univoltine in contrast to suggestions from a previous study. 2. Annual production determined by the size-frequency method ranged from 1.21 to 2.77g dry wt m"^ year"', and are the highest rates recorded for this species in temperate waters. 3. Turnover rates (P/B ratios) ranged from 2.27 to 3.48 and are among the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Milstead & Threlkeld (1986) also found Hyalella to be capable of maintaining a fairly constant turnover rate despite wide fluctuations in other demographic variables. Hyalella turnover rates do vary, however, across geographic regions through a strong dependence of voltinism on temperature (France, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Milstead & Threlkeld (1986) also found Hyalella to be capable of maintaining a fairly constant turnover rate despite wide fluctuations in other demographic variables. Hyalella turnover rates do vary, however, across geographic regions through a strong dependence of voltinism on temperature (France, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Sampling methods and data compilation are described in France & Stokes (1988) and France (1990). Derivation of production ecology metrics are detailed in France (1993).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[30] Unfortunately, in-stream vegetation is not measured as part of standard physical habitat assessments in California. [17] In the natural aquatic environment, Hyalella azteca lives in algal mats [31] , macrophyte beds [32] or rocky habitats. [33] Wienert [34] found that unlike many other genera of amphipods, Hyalella is not inclined to burrow into the substrate for shelter but rather finds shelter in branching aquatic plants such as Chara.…”
Section: Discussionmentioning
confidence: 99%